Factors associated with overactive bladder symptom improvement after 1 year of monthly percutaneous tibial nerve stimulation therapy. Issue 6 (20th May 2019) - Pincus, Joseph; Rostaminia, Ghazaleh; Chang, Cecilia; Gafni‐Kane, Adam; Goldberg, Roger P.
Abstract: Aims: To investigate patient characteristics associated with overactive bladder (OAB) symptom improvement after 1 year of monthly percutaneous tibial nerve stimulation (PTNS) therapy. Methods: This was a retrospective chart review of women who underwent PTNS for refractory OAB symptoms between January 2011 and December 2017 in our tertiary center. Patients who received 12 monthly PTNS maintenance treatments after achieving success with 12 weekly PTNS treatments were included in the study. Reports on subjective changes in urinary frequency, nocturia, and urgency urinary incontinence were submitted at each visit. Patients were categorized to symptom improve and no improve groups. A multivariate analysis was performed to identify patient characteristics that predicted symptomatic improvement. Results: Sixty‐six patients were identified. Average subjective improvement after 12 monthly sessions compared with 12 weekly sessions was 5.2% on a scale of −100% to +100%. A history of urogynecologic surgery remained a significant negative predictor of symptom change from 12 weekly sessions to 12 monthly treatment sessions (odds ratio, 0.19; P  = .01). Conclusions: OAB symptoms remain relatively stable after 12 monthly treatments of PTNS, as compared with the 12‐week time point. A history of urogynecologic surgery was a negative predictor of OAB symptom improvement in patients receiving monthly PTNS for at least 12 months.